Cell polarity and planar cell polarity (PCP) in spermatogenesis. (September 2018) - Chen, Haiqi; Mruk, Dolores D.; Lui, Wing-yee; Wong, Chris K.C.; Lee, Will M.; Cheng, C. Yan
Abstract: In adult mammalian testes, spermatids, most notably step 17–19 spermatids in stage IV–VIII tubules, are aligned with their heads pointing toward the basement membrane and their tails toward the tubule lumen. On the other hand, these polarized spermatids also align across the plane of seminiferous epithelium, mimicking planar cell polarity (PCP) found in other hair cells in cochlea (inner ear). This orderly alignment of developing spermatids during spermiogenesis is important to support spermatogenesis, such that the maximal number of developing spermatids can be packed and supported by a fixed population of differentiated Sertoli cells in the limited space of the seminiferous epithelium in adult testes. In this review, we provide emerging evidence to demonstrate spermatid PCP in the seminiferous epithelium to support spermatogenesis. We also review findings in the field regarding the biology of spermatid cellular polarity (e.g., head-tail polarity and apico-basal polarity) and its inter-relationship to spermatid PCP. Furthermore, we also provide a hypothetical concept on the importance of PCP proteins in endocytic vesicle-mediated protein trafficking events to support spermatogenesis through protein endocytosis and recycling.